Gaya Bahasa Iltifȃt dalam Ayat-Ayat ‘Itȃb dan Pengaruhnya bagi Penafsiran Alquran - Aqdi Rofiq Asnawi (AL QUDS : Jurnal Studi Alquran dan Hadis, 2020)
Iltifȃt Stylistic Feature in ‘Itȃb Verses and Their Influence on Qur’anic InterpretationThe grammatical shift in theQur’anic style, well-known by iltifat, indicates particular meanings so that the existence of this stylistic feature in verses can influence its interpretation. This paper, then, attempts to explore the influence further it makes by examining verses that contain reprimands (‘itab) in the Qur’an, verses of reprimand that use iltifat or not.The purpose of this study is to determine the extent of iltifat’s influence in the interpretation of the reprimand verses, namely in surah ‘Abasa (80) verses 1-11, compared with other reprimand verses that do not use the iltifat style. This study, then, applies a linguistic interpretation (al-tafsir al-lughawi) approach that analyzes verses based on the meaning of words, word order, and rhetorical aspects. This paper argues that the existence of the iltifat style in the reprimand verses refers to courtesy and exaltation. A sense of gentleness in fostering and educating is found as the influence of iltifat style on these verses